Early Warning and Monitoring of Coronavirus Disease 2019 Using Baidu Search Index and Baidu Information Index in Guangxi, China. Issue 4 (16th December 2022) - Xie, Yihong; Zhou, Wanwan; Zhu, Jinhui; Ruan, Yuhua; Wang, Xiaomin; Huang, Tengda
Abstract: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease, and it is important to detect early and monitor the disease trend for policymakers to make informed decisions. We explored the predictive utility of Baidu Search Index and Baidu Information Index for early warning of COVID-19 and identified search keywords for further monitoring of epidemic trends in Guangxi. A time-series analysis and Spearman correlation between the daily number of cases and both the Baidu Search Index and Baidu Information Index were performed for seven keywords related to COVID-19 from January 8 to March 9, 2020. The time series showed that the temporal distributions of the search terms "coronavirus, " "pneumonia" and "mask" in the Baidu Search Index were consistent and had 2 to 3 days' lead time to the reported cases; the correlation coefficients were higher than 0.81. The Baidu Search Index volume in 14 prefectures of Guangxi was closely related with the number of reported cases; it was not associated with the local GDP. The Baidu Information Index search terms "coronavirus" and "pneumonia" were used as frequently as 192, 405.0 and 110, 488.6 per million population, respectively, and they were also significantly associated with the number of reported cases ( r s > 0.6), but they fluctuated more than for the Baidu Search Index and had 0 to 14 days' lag time to the reported cases. The Baidu Search Index with search terms "coronavirus, " "pneumonia" and "mask" can be used for early warning and monitoring of the epidemic trend of COVID-19 in Guangxi, with 2 to 3 days' lead time.